2020
DOI: 10.1103/physrevb.102.195205
|View full text |Cite
|
Sign up to set email alerts
|

Optical determination of the band gap and band tail of epitaxial Ag2ZnSnSe4 at low temperature

Abstract: We report on the precise determination of both the band gap E g and the characteristic energy U of the band tail of localized defect states, for monocrystalline Ag 2 ZnSnSe 4. Both photoluminescence excitation and timeresolved photoluminescence studies lead to E g = 1223 ± 3 meV, and U = 20 ± 3 meV, at 6 K. The interest of the methodology developed here is to account quantitatively for the time-resolved photoluminescence and photoluminescence excitation spectra by only considering standard textbook density of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…This was previously observed for several spinels such as MgGa 2 O 4 :Co 2+ 43,44 , ZnGa 2 O 4 :Co 2+ 44,45 , and MgGa 2 O 4 :Cr 3+ 46 . Some authors showed results of bandgap calculation using PLE instead of UV-VIS absorption spectroscopy with results close to those obtained with absorption spectroscopy [47][48][49][50] . In this way, considering the possibility of the similarity between PLE and absorption spectra of the Mg 2 SnO 4 :Co 2+ , as seen in references [43][44][45] , the bandgap value for the Mg 2 SnO 4 :Co 2+ of the most emitting sample (0.08 at mol% of Co 2+ ) was estimated from PLE spectra.…”
Section: Photoluminescence Spectroscopysupporting
confidence: 53%
“…This was previously observed for several spinels such as MgGa 2 O 4 :Co 2+ 43,44 , ZnGa 2 O 4 :Co 2+ 44,45 , and MgGa 2 O 4 :Cr 3+ 46 . Some authors showed results of bandgap calculation using PLE instead of UV-VIS absorption spectroscopy with results close to those obtained with absorption spectroscopy [47][48][49][50] . In this way, considering the possibility of the similarity between PLE and absorption spectra of the Mg 2 SnO 4 :Co 2+ , as seen in references [43][44][45] , the bandgap value for the Mg 2 SnO 4 :Co 2+ of the most emitting sample (0.08 at mol% of Co 2+ ) was estimated from PLE spectra.…”
Section: Photoluminescence Spectroscopysupporting
confidence: 53%
“…In 1966, Tauc and his team further simplified the law into a power equation, which has become known today as Tauc’s law. An optical reflection spectra can be used to estimate the E g of semiconductors using Tauc’s method, which is applicable to both amorphous and crystalline nanomaterials. …”
Section: Introductionmentioning
confidence: 99%